Estudo das comunidades de pequenos mamíferos terrestres da Mata Atlântica : diversidade beta e funcional - Gurgel Filho, Newton Mota (2016)
The Brazilian Atlantic Forest is one of the most diverse and threatened biomes, considered a global biodiversity hotspot. It has about 40% of the diversity of mammals in Brazil. Noteworthy are the small mammals belonging to Rodentia and Didelphimorphia taxa. These groups are frequent targets of studies on alpha diversity patterns and factors that determine their geographical distribution. Complementary approaches such as β (beta) or functional diversity are scarce. Thus, this research aimed to study the patterns β and functional diversity of the small mammal’s communities of the Brazilian Atlantic Forest based on species distribution databases, and investigate its correlation with climate and spatial variables. High turnover values were obtained for the small mammal’s communities of the Atlantic Forest, with a significant nestedness contribution only for Marsupials. There is evidence to consider the Atlantic divided into two distinct areas, one north and one south. These diversity patterns are related to climate and spatial factors. Functional Diversity shows great variation, with Rodents and Marsupials complemented functionally. The rodent communities are structured by limiting similarity. Marsupials are under environmental filtering in the northern part of the Atlantic Forest. Additionally, it was found that Marsupials and Rodents and must be analyzed separately to avoid obscuring the intrinsic patterns of each phylogenetic group.